Metal artefacts in MRI-guided brachytherapy of cervical cancer - Soliman, Abraam S.; Owrangi, Amir; Ravi, Ananth; Song, William Y. (Journal of Contemporary Brachytherapy, 2016)
The importance of assessing the metal-induced artefacts in magnetic resonance imaging (MRI)-guided brachytherapy is growing along with the increasing interest of integrating MRI into the treatment procedure of cervical cancer. Examples of metal objects in use include intracavitary cervical applicators and interstitial needles. The induced artefacts increase the uncertainties in the clinical workflow and can be a potential obstacle for the accurate delivery of the treatment. Overcoming this problem necessitates a good understanding of its originating sources. Several efforts are recorded in the literature to quantify the extent of such artefacts, in phantoms and in clinical practice. Here, we elaborate on the origin of metal-induced artefacts in the light of brachytherapy applications, while summarizing recent efforts that have been made to assess and overcome the induced distortions.